WORKSHOP DISPLAY KELAS UNTUK MENINGKATKAN MOTIVASI SISWA DALAM MENGIKUTI PELAJARAN IPS SE-KECAMATAN LAMPIHONG - Syarifuddin Syarifuddin (Bestari: Jurnal Pengabdian Kepada Masyarakat, 2021)
Abstrak. Workshop activities like this really help teachers in developing students' imaginative abilities, and can increase students' motivation to always attend school, because schools become interesting and full of students' work with teachers. The materials used for making displays are very easy to obtain, so there are no more obstacles in their implementation. Teachers are assisted by KKN students in planning, making and displaying displays.